Nanodisplacement measurements of piezoelectric flextensional actuators using a new interferometry homodyne method - Galeti, Jose H. [UNESP]; Higuti, Ricardo T. [UNESP]; Silva, Emilio C. N.; Kitano, Claudio [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2015)
Piezoelectric flextensional actuator (PFA) devices are increasingly being applied in precision mechanics, such as nanotechnology equipments, electronic microscopy instruments, cell manipulation systems, and microsurgery tools. These PFAs need to be characterized by measuring the produced nanodisplacements, and optical interferometry is well established as an accurate and precise technique for this application. In this paper, a new and efficient method for optical phase detection, here named generalized J(1)/J(3) method, is presented. As in the J(1)/J(3) conventional method, the new method is based on information contained in the photodetected signal spectrum when the drive voltage is sinusoidal and has a known frequency. The dynamic range of this method is from 0.26 to 100 pi rad (and higher), and only a limited number of frequencies in the magnitude spectrum of the photodetected signal are used, without the need to know the phase spectrum. The method has the advantages of being simple, passive homodyne, self-consistent, and immune to fading. Using the new method, two novel PFAs prototypes, designed using topology optimization method, are tested in terms of displacement linearity (relative to applied voltage) and frequency response.
Keywords: Harmonic analysis; Optical interferometry; Phase detection; Piezoelectric transducers; Vibration measurement